2009
DOI: 10.1136/adc.2008.149674
|View full text |Cite
|
Sign up to set email alerts
|

Oral calcium supplementation reverses the biochemical pattern of parathyroid hormone resistance in underprivileged Indian toddlers

Abstract: From these data the authors conclude that low dietary calcium intake is associated with resistance to PTH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In the study population, 71 % girls showed iCa concentration below the reference range, whereas high concentrations of PTH ( > 6.4 p M ) (33) were observed in 39.5 % of the girls. In the study population, 71 % girls showed iCa concentration below the reference range, whereas high concentrations of PTH ( > 6.4 p M ) (33) were observed in 39.5 % of the girls.…”
Section: Resultsmentioning
confidence: 75%
“…In the study population, 71 % girls showed iCa concentration below the reference range, whereas high concentrations of PTH ( > 6.4 p M ) (33) were observed in 39.5 % of the girls. In the study population, 71 % girls showed iCa concentration below the reference range, whereas high concentrations of PTH ( > 6.4 p M ) (33) were observed in 39.5 % of the girls.…”
Section: Resultsmentioning
confidence: 75%
“…On the other hand, several cases of PHP‐Ia with documented GNAS mutations have been reported in whom PTH levels were elevated during infancy . Moreover, although the presence of GNAS mutations was not investigated, hypocalcemia owing to PTH resistance has been reported in a substantial number of infants and newborns . Hence, it has remained unclear whether the renal proximal tubular PTH resistance caused by maternal loss of Gαs manifests itself during early postnatal life.…”
Section: Introductionmentioning
confidence: 99%
“…This characteristic implies that there is resistance to the activity of PTH in the renal tubules. There is evidence to suggest that this phenotype occurs as a consequence of dietary calcium deficiency, which corrects when adequate calcium intake is supplied [37] .…”
Section: Vitamin D Deficiencymentioning
confidence: 99%